High thermoelectric efficiency of p-type BiSbTe-based composites with CuGaTe2 nanoinclusions. (November 2019) - Li, Yuanyue; Wang, Xiaocui; Liu, Guoxia; Shin, Byoungchul; Shan, Fukai
Abstract: To improve thermoelectric figure of merit ( ZT ) of BiSbTe and achieve a large average ZT ave in a broad range of temperatures is significant for energy harvesting from low-grade waste heat. In this report, we show that in CuGaTe2 /BiSbTe nanocomposites, both enhanced power factor and reduced thermal conductivity are simultaneously realized at elevated temperatures, owing to the energy filtering effect, reduced bipolar effect and strengthened phonon scattering. Consequently, an average ZT ave of 1.36 and an excellent projected conversion efficiency of 9.5% in the temperature range of 300–500 K are achieved for the composites incorporated with 0.4 vol .% CuGaTe2 nanoinclusions. Graphical abstract: Unlabelled Image